The contributing role of family, religious activities and school in protecting the mental well-being of school going adolescents in a rural district of Sri Lanka - N. H. S. Nadeeka; Kumudu Wijewardena (College of Community Physicians of Sri Lanka, 2023)
Introduction: Mental health problems in adolescence are common. Objectives: To assess the mental health of grade 10 students in Ampara District and their associated factors Methods: This descriptive study was conducted from May to November 2018. Strengths and Difficulties Questionnaire (SDQ) was used to assess the students' mental health status under five domains. They were total abnormal scores (TAS), emotional problems (EP), conduct problems (CP), hyperactive/inattention problems (HIP) and peer problems (PP). The prevalence of mental health problems was summarized as percentages. The significance of associated factors was assessed at p<0.05 and presented in adjusted odds ratio (aOR). Results: Of the 1340 students, 11.9% had reported TAS. The prevalence of EP, CP, PP and HIP were 15.1%, 12.9%, 12.1% and 11.7%, respectively. Eight factors associated with abnormal scores were identified. Difficulties in schoolwork were associated with all five domains (aOR=5.9; 95% CI: 2.5, 13.6 for TAS; aOR=4.0; 95% CI: 2.1, 7.7 for EP, aOR=2.9; 95% CI: 1.6, 5.4 for CP, aOR =2.6; 95% CI: 1.4, 4.6 for PP and aOR=2.5; 95% CI: 1.4, 4.5 for HIP). Not involving in religious activities regularly at home was associated with all domains except emotional problems (aOR=2.4; 95% CI: 1.3, 4.3 for TAS, aOR=2.2; 95% CI: 1.2, 3.9 for PP, aOR=2.1; 95% CI: 1.2, 3.6 for HIP and aOR=1.9; 95% CI: 1.2, 3.5 for CP). Not having a close family member to discuss their problems was associated with TAS (aOR=2.4; 95% CI: 1.4, 4.2), EP (aOR=3.4; 95% CI: 1.9, 5.8) and HIP (aOR=2.2; 95% CI: 1.3, 3.7). The presence of stressful life events was associated with TAS (aOR= 1.9; 95% CI: 1.1, 3.4), EP (aOR=1.9; 95% CI: 1.1, 3.5) and CP (aOR=2.3; 95% CI: 1.3, 4.3). Tobacco smoking habit of father was associated with TAS (aOR=2.9; 95% CI: 1.2, 6.6) and CP (aOR=2.3; 95% CI: 1.1, 4.6). The alcohol-drinking habit of father was associated with EP (aOR=3.0; 95% CI: 1.3, 7.0). Not attending to additional tuition classes was associated with EP (aOR=1.9; 95% CI: 1.1, 3.4) and PP (aOR=2.6; 95% CI: 1.4, 4.6). The low educational level of the mother was associated with the TAS (aOR=1.9; 95% CI: 1.2, 3.4). Conclusions & Recommendations: Mental health problems are common among school-going adolescents. All mental health problems were significantly associated with difficulties in schoolwork and most of the others were modifiable family-related factors. School mental health screening programmes are recommended with special attention on students with difficulties in schoolwork. School Mental health awareness and promotional programmes should target the students as well as teachers and parents to create a supportive school and family environment.